SULT2A1 Gene Copy Number Variation is Associated with Urinary Excretion Rate of Steroid Sulfates - Schulze, Jenny (Frontiers Media S.A., 2013)
Human cytosolic sulfotransferases (SULT) 2A1 is the main enzyme involved in the sulfate conjugation of dehydroepiandrosterone, a weak androgen, and the main androgen precursor, whereas estrogens are mainly conjugated by SULT1A1. Here we have identified a copy number variation (CNV) polymorphism in the SULT2A1 gene in a Swedish population including healthy men (N = 30). Moreover, the CNV of SULT1A1 and SULT2A1 was further characterized in relation to urinary levels of androgen sulfate metabolites before and after an intramuscular dose of 500 mg testosterone enanthate. Individuals expressing two or more CNVs excrete 80 and 40% higher levels of DHEAS (p = 0.02) and androsteroneS (p = 0.01), respectively as compared to individuals with one gene copy. The mean area under the urine concentration time-curve from time 0 (prior to the administration of 500 mg testosterone) to 15 days post dose values were 80% higher for DHEAS (p = 0.046) and testosteroneS (p = 0.019) in individuals with two and three SULT2A1 gene copies as compared to individuals with one gene copy. The SULT1A1 CNV on the other hand did not affect the sulfation activity toward the androgens. In conclusion our results indicate that functional CNV polymorphisms in SULT2A1 and SULT1A1 are common in a Swedish population and that SULT2A1 CNV is associated with the urinary concentrations of androgen sulfate metabolites.